Airborne DOAS measurements over the South African highveld - Broccardo, Stephen Paul (My University, 2015)
An imaging DOAS instrument, along with in situ trace-gas and aerosol instrumentation was deployed on board a research aircraft over the Highveld region of South Africa, to make regional-scale measurements of nitrogen dioxide (NO2). The presence of a “hotspot” of NO2 over the Highveld is confirmed. Case-study estimates of NO2 emission flux were made downwind of a power station (10 tons.hr−1), a petrochemical plant (36 tons.hr−1) and the entire Highveld region (395 tons.hr−1). Vertical profile measurements were used to develop scenarios for a radiative transfer sensitivity study. From this, suitable air-mass factors for the DOAS measurements were determined. Comparisons between the airborne DOAS and satellite instruments show a good agreement where the spatial scales of the satellite ground pixels and the features in the two-dimensional trace-gas distribution are matched. A long-term record of satellite data was analysed. Analysis of radiative transfer revealed a possible artefact in the adjacent positive and negative trends evident on the Highveld. A correction to the satellite record for a seasonal bias was made, and found to be important over biomass burning regions in Angola and Zambia. Spatial features in a seasonal model of the satellite record are shown to correspond with known urban, industrial and biomass burning sources in the region. Signatures of soil emissions are also detected.
A thesis submitted to the Faculty of Geography, Archaeology, and Environmental Studies University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Doctor of Philosophy. 2015.
Keywords: Air--Pollution--Measurement.; Aerosols.